INNOVATION TOWARDS BUSINESS SUCCESS IN ULOS WEANING CRAFTSMAN MSMES IN TARUTUNG DISTRICT - Nana Khairani; Ade Indah Sari; Arasy Ayu (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2023)
This research aims to determine the influence of innovation on business success. This type of research is descriptive, the collection of information was obtained from sources at the Tarutung Subdistrict Office and interviews with ulos weaving craftsmen in Tarutung subdistrict, with the research population being all weavers in Tarutung subdistrict, the number The exact number of the population in this study is not known, so a research sampling technique was applied using cluster random sampling technique, namely, Ulos weaving craftsmen MSMEs located in 5 sub-districts in Tarutung, with 20 UKMs in each sub-district so that the total number is 100 UKMs as sample. The analysis technique used is MSR (Moderated Simple Regression). The results of the research show that innovation has a positive and significant effect on the business success of Ulos weaving craftsmen MSMEs in Tarutung sub-district.